(untitled) (Journal of Sciences & Technology, 2020)
The retention of copper ions from a synthetic solution by nanofiltration and reverse osmosis has been shown to be a feasible process to achieve efficient copper extraction. In this study, we investigate the effect of varying pressure, pH, and copper acetate concentration. The experimental results indicated that the retention of copper ions increase with increasing operating pressure, decrease with increasing concentration and were strongly influenced by the pH of the feed solution. Higher degrees of copper extraction were obtained for experiments carried out by reverse osmosis than those carried out by nanofiltration. The results show that, the extraction efficiency of copper by reverse osmosis varied from 90% to 100 % for an initial feed concentration of 50 ppm, and by nanofiltration ranged from 49 % to 98% and from 24% to 73 % for an initial feed concentration of 50 and 75 ppm, respectively.